Evolution and irreversibility: Two distinct phenomena and their distinct laws of nature - Bejan, A.; Almahmoud, H.; Gunes, U.; Fakhari, H. E.; Mardanpour, P. (ELSEVIER, 2024)
To clarify the place of time direction of change in nature (time arrow), the present article shows why Evolution and Irreversibility are two distinct phenomena. Their distinct laws of nature are the Constructal Law and the Second Law, respectively. The demonstration is based on the simplest setting imaginable: a solid body moving in a pool of water. The view is holistic: the system selected for analysis is the body and the pool, not the body alone, and the phenomenon is the evolution of the image (configuration) of the whole. New is also the answer to the question of what flows in this evolving flow configuration. Along the way, important terms are defined: phenomenon, law, irreversibility, nature, design, freedom, theory versus empiricism, information, knowledge, selection, purpose, engine, refrigeration, and wheel. More complex natural settings for the demonstration are in the second part of the article: engines, refrigeration, heating and cooling, the wheel, and a pushed boat sliding on water.
Keywords: Evolution; Time; Change; Irreversibility; Second law; Constructal law; Freedom; Swimming; PEDESTRIAN DYNAMICS LOCOMOTION; UNIFYING CONSTRUCTAL THEORY; SELF-ORGANIZATION; WALKING PATHS; FLOW SYSTEMS; DESIGN; ENERGY; EMERGENCE; SIZE; Life Sciences & Biomedicine - Other Topics; Biophysics